IoT Based Green Computing: An Attempt to Delineate E-Waste Management - Dr. V. Ramanujam, Dr. D. Napoleon (International Journal of Advanced Science and Technology, 2020)
Owing to the hasty advancement in science and technology the world turns "insolent". Due to proliferation of cost and demand tramp for energy makes us to find a new-fangled way to save energy. The subsequent whirling in human history, the intelligent world gets a lot of attention from academies, conglomerates, administrations and so on. As a final point the people in the intellectual world will be interconnected and intelligent. Internet of Things helps in assimilating and relating the physical devices to the Internet without any human intervention and human to human or human to computer interaction. It represents the next biggest revolution towards the forthcoming future in the Information and Technological world where Green computing brings the ecological responsibility with sustainable use of computers and their resources. In broader terms the using and disposing of computing devices in a way that reduces their environmental impact. In this paper tabloid quite a lot of green initiatives have been outstretched regarding these initiatives and presents a study about the green computing and e-waste recycling process.  The technology based devices may help the environment to be protected. For cost effective and efficient waste collection there is a need of technology based devices. In this paper IOT enabled garbage collection system has been proposed. This paper presents a technique to detect the real time level of garbage in the dustbins. The level is sensed with the help of IR sensors and communicated to the authority through buzzer installed at their office. This methodology converts the dustbins into a smart dustbin which can be connected with the eventually green computing emphases on ways in tumbling overall environmental impact which promotes a new way of reducing pollution, discovering alternative technologies, and creating more recyclable products. We fashioned expertise make convinced that it doesn't annihilate us.